Design and fabrication of multilayer inkjet-printed passive components for printed electronics circuit development. (January 2018) - Correia, V.; Mitra, K.Y.; Castro, H.; Rocha, J.G.; Sowade, E.; Baumann, R.R.; Lanceros-Mendez, S.
Graphical abstract: Highlights: A multilayer approach is used for the fabrication of passive electronic components. The fabrication has been performed achieved by ink-jet printing. Resistors, inductors and capacitors were fabricated. It is possible to manufacture tailored passive circuit elements by ink-jet printing. Abstract: Printing electronic passive components suffers from the lack of a wide variety of appropriate materials for developing components with specific characteristics and for specific dimensions. This paper introduces a multilayer approach for the inkjet printing of resistors, inductors and capacitors. The materials and process steps for the manufacturing, the individual component characteristics and the equivalent circuit is provided for all passive devices. It is shown that the multilayer approach is a suitable strategy for manufacturing inkjet printed passive circuit elements with tailored characteristics for implementation into functional printed electronics devices.